Regulation of Broadcast Indecency : Background and Legal Analysis. (U.S. Congressional Research., 2005)
Provides background on and discusses the evolution of FCC regulations prohibiting TV and radio broadcasts of indecent material during certain hours. Outlines recent events focusing attention on FCC indecency regulations, analyzes current regulations, reviews various FCC actions regarding indecency, and summarizes related Congressional activity. Examines whether prohibiting the broadcast of indecent words in any context would violate the First Amendment.